Results of the ground penetrating radar survey in the church of St. Elias — Bohdan Khmelnytsky burial vault in Subotiv - Bondar, K. M.; Khomenko, R. V.; Chernov, A. P.; Kuksa, N. V. (Geofizicheskiy Zhurnal, 2020)
Archaeogeophysical investigations in the Church of St.Elias in Subotiv (Cherkasy region, Ukraine) were conducted in the course of critical revision of the historical myth that exists around this monument, known as the burial vault of Bohdan Khmelnytsky, Hetman of the Zaporozhian Cossack Army and the founder of the Ukrainian state. The aim of the study was to search for hidden structures in the walls and under a floor of the Church. The paper presents investigation that combined georadar (GPR) survey, preceded by a careful review of historical and archaeological sources, and then followed up with forward modelling and test drilling to verify and supplement the geophysical results. The measurements were carried out using VIY-3 georadars operating at 300 and 500 MHz frequency by floor of the nave and by walls of the south-west corner of the church. In the central part of the church, at the depths of 2.4 and 4.0 m, anomalies were identified from the vault and the floor of the underground structure, stretching along E-W direction, which is probably almost completely filled with soil. Drilling at the place of anomaly has confirmed presence of decompacted zone corresponding to infill. Synthetic radargrams calculated using the GprMax program, using geometric parameters of the object interpreted from the GPR data and the physical properties of soils measured by independent methods, have close simularity with those observed. No large cavities were found in the walls of the southwestern corner utilizing GPR method. Taking into consideration the inconsistency of the chronicle version about the destruction of the grave of B. Khmelnytsky by Polish szlachta troops in 1664, the structure may appear to be his burial crypt, whose presence is evidenced in written historical sources.